Preparation method and application of antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness
By adding hollow copper sulfide nanoparticles and EGCG to the antibacterial hydrogel, combined with near-infrared light irradiation and pH response, the problems of limited antibiotic resistance and wound healing materials in the prior art are solved, and efficient and safe antibacterial and wound repair effects are achieved.
Patent Information
- Application Number
- CN202411481251.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art has high risk of antibiotic resistance in treating bacterial wound infections, and traditional wound healing materials have limited effects due to inflammatory responses and oxidative stress effects, making it difficult to achieve efficient and safe antibacterial and wound repair.
An antibacterial hydrogel with enhanced antioxidant activity and NIR/pH dual response characteristics was adopted. By adding hollow copper sulfide nanoparticles and epigallocate gallate (EGCG) to the hydrogel, combined with 808nm near-infrared light irradiation and pH response, a synergistic antibacterial effect was achieved.
The hydrogel shows strong antibacterial ability in high concentration bacterial environments, can play an advantage in the healing process of bacterial wound infection, and has good mechanical properties, injectability and biocompatibility.
Smart Images

Figure CN119548663A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to hydrogel, in particular to a preparation method and application of antibacterial hydrogel as a biomedical material, belonging to the technical field of chemistry. Background Art
[0002] Bacterial wound infection is one of the serious threats to public health. Traditional clinical treatments have caused the risk of drug-resistant bacteria due to over-reliance on antibiotics. In addition, the wound healing process (hemostasis, inflammation, proliferation, remodeling) will be disturbed and biochemically disturbed by inflammatory response, oxidative stress effect, rapid matrix degradation, etc. Therefore, it is urgent to develop new antibacterial strategies and wound healing materials to fight bacterial infection in a more effective and safer way, while repairing damaged skin more gently and accelerating wound healing. As a wound dressing, hydrogels have a unique three-dimensional network structure that can not only absorb wound exudate and maintain a moist wound environment, but also accurately release drugs locally to achieve therapeutic effects. In recent years, photothermal water gels have attracted widespread attention due to their excellent photoresponsiveness and thermal conversion capabilities. However, single photothermal therapy (PTT) requires higher temperatures to effectively fight bacteria, which may cause secondary damage to damaged tissues. In order to overcome the above limitations, people are more concerned about the synergistic effects of other antibacterial strategies (such as photodynamic therapy (PDT), chemodynamic therapy (CDT) or natural drug treatments) to achieve excellent therapeutic effects at lower temperatures or shorter treatment times. Therefore, it is imperative to develop a multifunctional antibacterial hydrogel dressing platform based on photothermal therapy. The use of reversible bonds as crosslinkers in the fields of tissue engineering and flexible devices can prepare hydrogels with excellent mechanical properties and healing properties, which is a promising strategy. For example, a complex formed by the catechol structure and borate in halogenated catechol was used as a crosslinker to synthesize a hydrogel that can dissociate at acidic pH and condense at alkaline pH, showing good self-healing properties and antibacterial activity. However, this halogenated catechol inevitably has the disadvantage of greater cytotoxicity. Therefore, the development of a pH-responsive hydrogel dressing containing natural drugs with excellent mechanical properties, self-healing properties, and good biocompatibility is conducive to meeting the clinical needs of wound treatment. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art, and proposes a method for preparing an injectable antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual response characteristics for promoting wound healing at bacterial infection sites. The hydrogel has good mechanical properties, injectability, adhesion, pH responsiveness, and antioxidant properties, and has broad application prospects.
[0004] To achieve the purpose of the present invention, the following technical scheme is adopted: a method for preparing an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness, the preparation method is as follows: firstly, hollow copper sulfide nanoparticles are prepared, and then the hollow copper sulfide nanoparticles are dispersed in a chitosan solution to prepare a chitosan solution containing hollow copper sulfide nanoparticles, and then a crosslinking agent epigallocatechin gallate (EGCG) solution and a 3-formylphenylboronic acid solution (3-FPBA) are sequentially added for crosslinking to obtain an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness.
[0005] Further; the preparation steps are as follows: A: CuCl 2 The solution and PVP-K30 were added to deionized water, stirred magnetically at room temperature, and NaOH solution was added. After 2 min, N 2 H 4 ·H 2 O, and Na was added after 5 min 2 S solution, reacted at 75 °C for 2 h to generate hollow copper sulfide nanoparticles, and finally centrifuged at 12000 rpm for 10 min, washed three times with secondary water, and the hollow copper sulfide nanoparticles were collected; B: Chitosan was dissolved in deionized water, and glacial acetic acid solution was added under shaking to dissolve it, and then sodium hydroxide solution was added to adjust the pH value of the prepared chitosan solution to neutral. EGCG and 3-formylphenylboronic acid were dissolved in deionized water to obtain 1.5% EGCG solution and 0.065M 3-formylphenylboronic acid solution respectively; C: The copper sulfide nanoparticles obtained in A were uniformly mixed into the chitosan solution obtained in B to prepare a 3% chitosan solution containing hollow copper sulfide nanoparticles, and then equal volumes of EGCG solution and 3-formylphenylboronic acid solution were added in sequence, and the mixture was mixed on a mixer for 30 seconds to obtain an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual response characteristics; In the above method, steps A and B are performed in no particular order.
[0006] Further; in step A, CuCl 2 The concentration is 0.5 mol / L, the concentration of NaOH solution is 0.01mM, Na 2 The concentration of S solution is 320 mg / mL.
[0007] Furthermore, in step B, chitosan is dissolved in 2% glacial acetic acid solution, and finally a 3% chitosan solution is prepared.
[0008] Furthermore, in step C, the mass percentage concentration of the hollow copper sulfide nanoparticles in the chitosan solution is 43.75~350 µg / mL.
[0009] Application of an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness, wherein the hydrogel is used for wound dressing in biomedical engineering materials.
[0010] Furthermore, when used as wound dressing, the concentration of hollow CuS NPs was 125 μg / mL.
[0011] Further, when used as a wound dressing, the power density is less than or equal to 2 W cm -2 808nm near-infrared laser irradiation.
[0012] The positive and beneficial technical effects of the present invention are: the preparation method of the present invention is simple, the gelation time is short, the preparation process is green and safe, the hollow copper sulfide nanoparticles are synthesized, the operation is simple, the photothermal effect and biocompatibility of the nanoparticles are excellent, and due to the loading of copper sulfide nanoparticles in the hydrogel, the mechanical properties of the hydrogel are higher than those of the simple EGCG hydrogel, and the hydrogel exhibits higher solid-like properties while also maintaining excellent injectability. Under the irradiation of 808nm near-infrared light, through the synergistic effect of PTT and EGCG, the hydrogel still exhibits strong antibacterial ability even under high concentrations of bacteria, and can play a greater advantage in the healing process of bacterial wound infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a schematic diagram of the gelation principle of the CuS@EGCG hydrogel and the EGCG hydrogel of the present invention.
[0014] Figure 2 This is a scanning electron microscope image of the end surface of the EGCG hydrogel in Example 1.
[0015] Figure 3 This is the end-face scanning electron microscope image of the CuS@EGCG hydrogel of Example 1 and the Cu and S element distribution map for the region.
[0016] Figure 4 This is the stress-strain curve of the CuS@EGCG hydrogel and the EGCG hydrogel in Example 2.
[0017] Figure 5 Schematic diagram of self-healing of CuS@EGCG hydrogel in Example 2.
[0018] Figure 6 Schematic diagram of the injectable CuS@EGCG hydrogel of Example 2.
[0019] Figure 7The photothermal effect diagram of CuS@EGCG hydrogel in Example 3, photothermal conversion of water (a), chitosan solutions of different concentrations (b), EGCG hydrogels of different concentrations (c), and CuS@EGCG hydrogels of different concentrations under 808 laser (2W / cm2) irradiation (31.25μg / mL (d), 62.5μg / mL) (e), 100 μg / mL (f), 125μg / mL) (g), and 250μg / mL) (h).
[0020] Figure 8 The power density of near-infrared irradiation is (a) 0.5, (b) 1, (c) 1.25, (d) 1.5 and (e) 1.75, (f) 2 W / cm 2 ) under temperature change of CuS@EGCG hydrogel.
[0021] Fig. 9 CuS@EGCG hydrogel was exposed to near-infrared irradiation (10 min, 2 W / cm 2 ) Heating and cooling curves under on / off cycles (3 times).
[0022] Fig.10 Schematic diagram of the scavenging of ABTS free radicals by CuS@EGCG hydrogel and EGCG hydrogel.
[0023] . Fig.11 Schematic diagram of DPPH free radical scavenging by CuS@EGCG hydrogel and EGCG hydrogel.
[0024] Fig.12 This is the pH responsiveness verification diagram of CuS@EGCG hydrogel and EGCG hydrogel in Example 3.
[0025] Fig.13 This is one of the antibacterial verification figures of CuS@EGCG hydrogel and EGCG hydrogel in Example 3.
[0026] Fig.14 This is the second figure of the antibacterial verification of CuS@EGCG hydrogel and EGCG hydrogel in Example 3. DETAILED DESCRIPTION
[0027] In order to more fully explain the implementation of the present invention, implementation examples of the present invention are provided. These implementation examples are merely elaborations of the present invention and do not limit the scope of the present invention.
[0028] In the present application, H-CuS NPs refers to hollow copper sulfide nanoparticles, CuSNPs refers to copper sulfide nanoparticles, H- represents hollow; CuS@EGCG hydrogel refers to the product of the present application, an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness; CS refers to chitosan; 3-FPBA refers to 3-formylphenylboronic acid; EGCG refers to epigallocatechin gallate; A method for preparing an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness, the preparation steps are as follows: A: A: CuCl 2 Solution and PVP-K30 were added to deionized water, the ratio of deionized water to PVP-K30 was 1mL:9-10mg; CuCl 2 The concentration is 0.5 mol / L, CuCl 2 The ratio of PVP-K30 was 1 µmol:4.5-5 mg. Under magnetic stirring at room temperature, NaOH solution was added, the concentration of NaOH solution was 0.01 mM, and the volume was equal to that of deionized water. After 2 min, N 2 H 4 ·H 2 O,N 2 H 4 ·H 2 The ratio of O to PVP-K30 was 1 µL: 37-37.5 mg; after 5 min, Na 2 S solution, Na 2 The mass ratio of S to PVP-K30 was 3.5-4: 1; the reaction was carried out at 75°C for 2 h to generate hollow copper sulfide nanoparticles, and finally the hollow copper sulfide nanoparticles were collected by centrifugation at 12000 rpm for 10 min and washed three times with secondary water; B: Chitosan was dissolved in deionized water, and glacial acetic acid solution was added under shaking to dissolve it, and then sodium hydroxide solution was added to adjust the pH value of the prepared chitosan solution to neutral. EGCG and 3-formylphenylboronic acid were dissolved in deionized water to obtain 1.5% EGCG solution and 0.065M 3-formylphenylboronic acid solution respectively; C: The copper sulfide nanoparticles obtained in A were uniformly mixed into the chitosan solution obtained in B to prepare a 3% chitosan solution containing hollow copper sulfide nanoparticles, and then equal volumes of EGCG solution and 3-formylphenylboronic acid solution were added in sequence, and the mixture was mixed on a mixer for 30 seconds to obtain an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual response characteristics; In the above method, steps A and B are performed in no particular order.
[0029] Further; in step A, CuCl 2The concentration is 0.5 mol / L, the concentration of NaOH solution is 0.01mM, Na 2 The concentration of S solution is 320 mg / mL.
[0030] Furthermore, in step B, chitosan is dissolved in 2% glacial acetic acid solution, and finally a 3% chitosan solution is prepared.
[0031] Furthermore, in step C, the mass percentage concentration of the hollow copper sulfide nanoparticles in the solution is 50-200 µg / mL.
[0032] Example 1 This embodiment provides an injectable antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual response characteristics, the preparation of which includes the following steps: 1) Preparation and morphology characterization of hollow copper sulfide nanoparticles: 28 μL CuCl2 solution (0.5 mol / L) and 67.2 mg PVP-K30 were added to 7 mL deionized water and magnetically stirred at room temperature. An equal volume of NaOH solution (0.01 mM) was added, and 1.8 μL N 2 H 4 ·H 2 O, and Na was added after 5 min 2 56 μL of S solution (concentration of 320 mg / mL) was reacted at 75°C for 2 h to generate CuS NPs. The hollow CuS NPs were collected by centrifugation at 12000 rpm for 10 min and deionized washing twice.
[0033] 2) Preparation of CuS@EGCG hydrogel and EGCG hydrogel: 0.3 g chitosan powder was dissolved in acetic acid solution (10 mL, 2% (v / v)) to prepare 3% (w / v) CS solution. After the chitosan was completely dissolved, a certain amount of 6 M NaOH was added to make the solution pH about 7. Then, 0.06 g EGCG and 0.039 g 3-formylphenylboronic acid were dissolved in 4 mL ethanol solution (40% (v / v)) to obtain 0.015 g / mL and 0.065 M solutions, respectively. The prepared solutions were mixed in the ratio of CS solution: EGCG solution: 3-FPBA solution = 5:1:1, and then the whole mixture was vortexed for 30 seconds to obtain EGCG hydrogel; The steps for synthesizing CuS@EGCGHY are to add the hollow CuS NPs solution into the CS solution to obtain 3% (w / v) The CS solution is then mixed with the EGCG solution and the 3-FPBA solution and subsequent steps are performed to complete the preparation.
[0034] See also Figure 1Shown is the schematic diagram of the gelation principle of CuS@EGCG hydrogel and EGCG hydrogel.
[0035] The EGCG hydrogel prepared in Example 1 was examined by scanning electron microscopy (SEM). Figure 2 and CuS@EGCG hydrogel Figure 3 To characterize, Figure 2 The network structure of the hydrogel is shown. Example 2
[0036] Example 2 Characterization of some mechanical properties of the prepared CuS@EGCG hydrogel and EGCG hydrogel (1) Preparation and morphology characterization of hollow copper sulfide nanoparticles: CuCl 2 The solution (28 µL, 0.5 mol / L) and PVP-K30 (67.2 mg) were added to 7 mL of deionized water and stirred magnetically at room temperature. NaOH solution (7 mL, 0.01 mM) was added, and 1.8 µL of N 2 H 4 ·H 2 O. After 5 min, Na 2 56 μL of S stock solution (320 mg / μL) was reacted at 75°C for 2 h to generate hollow CuS NPs. The hollow CuS NPs were collected by centrifugation at 12000 rpm for 10 min and deionized washing twice; (2) Preparation of CuS@EGCG hydrogel and EGCG hydrogel: 0.3 g chitosan powder was dissolved in acetic acid solution (10 ml, 2% (v / v)) to prepare 3% (w / v) CS solution. After the chitosan was completely dissolved, a certain amount of 6 M NaOH was added and the pH of the solution was about 7. Then EGCG and 3-formylphenylboronic acid were dissolved in 4 mL ethanol solution (40% (v / v)) to obtain 0.015 g / mL and 0.065 M solutions, respectively. The prepared solutions were mixed in the ratio of CS solution: EGCG solution: 3-FPBA solution = 5:1:1, and then the whole mixture was vortexed for 30 seconds to obtain EGCG hydrogel. The steps for synthesizing CuS@EGCGHY are to add the hollow CuS NPs solution into the CS solution to obtain 3% (w / v) CS solutions with different CuS concentrations, and then perform the steps of mixing with EGCG solution and 3-FPBA solution and the subsequent steps to complete the preparation.
[0037] In the amplitude sweep test, the rheological properties were determined using a rheometer (AR2000ex) with a fixed frequency sweep (1 Hz). Figure 4As shown in the figure, the storage modulus and loss modulus of CuS@EGCG hydrogel are higher than those of EGCG hydrogel; this is precisely due to the higher cross-linking density; among them, G′ and G″ of CuS@EGCG hydrogel intersect at the strain (about 400%), while the strain intersection point of EGCG hydrogel is around 277%, which reflects that the addition of copper sulfide nanoparticles makes the hydrogel have higher mechanical tolerance and exhibits better solid-like properties.
[0038] Self-healing and injectable properties: Figure 5 , Figure 6 As shown in Figure 2, the self-healing property of CuS@EGCG hydrogel is demonstrated macroscopically. Figure 6 In the experiment, CuS@EGCG hydrogel was continuously written on the culture dish using a 1mL syringe. CuS@EGCG hydrogel can be easily injected through a 0.45mm needle without clogging and healed quickly, which can adapt to irregular tissue defects. Example 3
[0039] In this example, the photothermal, antioxidant, pH response and antibacterial properties of the prepared CuS@EGCG hydrogel and EGCG hydrogel were characterized.
[0040] (1) Preparation and morphology characterization of hollow copper sulfide nanoparticles: 28 μL of CuCl2 solution (0.5 mol / L) and 67.2 mg of PVP-K30 were added to 7 mL of deionized water and stirred magnetically at room temperature. 7 mL of NaOH solution (0.01 mM) was added and N was added 2 min later. 2 H 4 ·H 2 O. After 5 min, Na 2 56 μL of S solution (concentration of 320 mg / mL) was reacted at 75°C for 2 h to generate hollow CuS NPs. The hollow CuS NPs were collected by centrifugation at 12000 rpm for 8 min and deionized washing twice.
[0041] (2) Preparation of CuS@EGCG hydrogel and EGCG hydrogel: 0.3 g chitosan powder was dissolved in acetic acid solution (10 ml, 2% (v / v)) to prepare a 3% (w / v) CS solution. After the chitosan was completely dissolved, a certain amount of 6 M NaOH was added to make the solution pH about 7. Then, 0.06 g EGCG and 0.039 g 3-formylphenylboronic acid were dissolved in 4 mL ethanol solution (40% (v / v)) to obtain 0.015 g / mL and 0.065 M solutions, respectively; the prepared solutions were mixed in the ratio of CS solution: EGCG solution: 3-FPBA solution = 5:1:1, and then the whole mixture was vortexed for 30 seconds to obtain EGCG hydrogel; the steps of forming CuS@EGCGHY were to add the hollow CuS NPs solution to the CS solution to obtain 3% (w / v) CS solutions with different CuS concentrations, and then perform the mixing with EGCG solution and 3-FPBA solution and the subsequent steps to complete the preparation.
[0042] See also Figure 7 The photothermal performance verification diagram of CuS@EGCG hydrogel is shown in the figure. As shown in the figure, the photothermal performance of CuS@EGCG hydrogel is closely related to the laser power density and the concentration of H-CuS NPs in the hydrogel. By comparing the −1 The temperature curve (h) of CuS@EGCG hydrogel at the concentration of 125 μg mL−1 (i.e., 125 μg / mL) was obtained. It was found that even if the concentration was doubled, the temperature curve was basically the same without obvious changes. Therefore, we selected the CuS@EGCG hydrogel with a H-CuS NPs concentration of 125 μg mL−1 (i.e., 125 μg / mL) for the subsequent condition investigation. Next, we investigated the effect of different power densities on the hydrogel. Figure 8 It can be seen that when the near-infrared laser power density is 2 W / cm 2 (2 W cm -2 ), the temperature of CuS@EGCG hydrogel increased from 25°C to 53°C after irradiation for 3 minutes at a power density of 2 W cm. In contrast, when the power density was less than this, the temperature could not rise to more than 50°C in a short time. In view of the fact that in photothermal therapy, temperatures exceeding 55°C will burn the body and cause secondary damage to the wound, thus hindering wound treatment, we finally determined the photothermal conditions of CuS@EGCG hydrogel: a power density of 2 W cm -2 The concentration of hollow CuS NPs was 125 μg mL −1, Photothermal stability is a very critical aspect to consider when evaluating photothermal agents (PTAs). -2The laser was then turned off for 5 minutes, and this heating and cooling cycle was repeated 3 times. Fig. 9 It can be seen that the temperature peak does not change much and the cooling trend is consistent, indicating that the photothermal performance of CuS@EGCG hydrogel is stable and repeatable during the cycle.
[0043] See also Fig.10 , Fig.11 Verification diagram of the antioxidant properties of CuS@EGCG hydrogel and EGCG hydrogel. The figure shows that compared with EGCG hydrogel, the introduction of H-CuS NPs in CuS@EGCG hydrogel significantly improved the hydrogel's ability to scavenge ABTS free radicals and DPPH free radicals, and has good biological application prospects.
[0044] See also Fig.12 The pH responsiveness verification diagram of CuS@EGCG hydrogel and EGCG hydrogel shown in the figure, by exploring the release rate of EGCG by the two hydrogels under pH = 4, 5, 6 and 7.4 conditions, it can be concluded that when the pH value is lower than 7.4, the release rate and release speed of the hydrogel will increase with the decrease of pH value, which can effectively achieve pH responsive treatment for changes in environmental pH during wound healing.
[0045] See also Fig.13 (Staphylococcus aureus), Fig.14 The antibacterial validation diagram of CuS@EGCG hydrogel and EGCG hydrogel shown in Figure 1 shows that when there is no near-infrared light (without NIR) irradiation, both hydrogels show limited antibacterial ability, and the survival rates of Staphylococcus aureus are 87% (EGCG HY) and 80% (CuS@EGCG HY), respectively. The vertical axis is the survival rate, and the survival rates of Escherichia coli are 82.5% (EGCG HY) and 67.8% (CuS@EGCG HY), respectively. The antibacterial performance of CuS@EGCG hydrogel is higher than that of EGCG hydrogel without near-infrared irradiation, which may be due to the hollow CuSNPs and Cu in the hydrogel. 2+ It is worth noting that after 3.5 min of near-infrared irradiation (with NIR), the bacterial survival rate of the CuS@EGCG hydrogel group was 0.056% (S. aureus) and 2.35% (E. coli), which had a significant bactericidal effect. This shows that the synergistic effect of photothermal and chemical antibacterial is conducive to killing bacteria faster and more efficiently, thus showing great potential in the field of wound dressings. control represents the blank control group.
[0046] After describing the implementation mode of the present invention in detail, people familiar with the technology can clearly understand that various changes and modifications can be made without departing from the scope and spirit of the above-mentioned patent application. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are within the scope of the technical solution of the present invention, and the present invention is not limited to the implementation mode of the examples given in the specification.
Claims
1. A method for preparing an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness, characterized in that The preparation method is as follows: hollow copper sulfide nanoparticles are first prepared, and then the hollow copper sulfide nanoparticles are dispersed in a chitosan solution to prepare a chitosan solution containing hollow copper sulfide nanoparticles, and then a cross-linking agent epigallocatechin gallate (EGCG) solution and a 3-formylphenylboronic acid solution (3-FPBA) are sequentially added for cross-linking to obtain an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness.
2. The method for preparing an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness according to claim 1, characterized in that The preparation steps are as follows: A: CuCl2 solution and PVP-K30 were added to deionized water, and then magnetically stirred at room temperature. NaOH solution was added, and N2H4·H2O was added after 2 min. Na2S solution was added after 5 min. The mixture was reacted at 75°C for 2 h to generate hollow copper sulfide nanoparticles. Finally, the mixture was centrifuged at 12000 rpm for 10 min, and washed with secondary water for 3 times to collect the hollow copper sulfide nanoparticles); B: Chitosan was dissolved in deionized water, and glacial acetic acid solution was added under shaking to dissolve it, and then sodium hydroxide solution was added to adjust the pH value of the prepared chitosan solution to neutral. EGCG and 3-formylphenylboronic acid were dissolved in deionized water to obtain 1.5% EGCG solution and 0.065M 3-formylphenylboronic acid solution respectively; C: The copper sulfide nanoparticles obtained in A were uniformly mixed into the chitosan solution obtained in B to prepare a 3% chitosan solution containing hollow copper sulfide nanoparticles, and then equal volumes of EGCG solution and 3-formylphenylboronic acid solution were added in sequence, and the mixture was mixed on a mixer for 30 seconds to obtain an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual response characteristics; In the above method, steps A and B are performed in no particular order.
3. The method for preparing an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness according to claim 2, characterized in that In step A, the concentration of CuCl2 is 0.5 mol / L, the concentration of NaOH solution is 0.01 mM, and the concentration of Na2S solution is 320 mg / mL.
4. The method for preparing an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness according to claim 2, characterized in that In step B, chitosan is dissolved in 2% glacial acetic acid solution, and a 3% chitosan solution is finally prepared.
5. The method for preparing an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness according to claim 2, characterized in that In step C, the mass percentage concentration of the hollow copper sulfide nanoparticles in the chitosan solution is 43.75-350 µg / mL.
6. Application of an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness, characterized in that: The hydrogel is used for wound dressing in biomedical engineering materials.
7. The use of an antibacterial hydrogel with enhanced antioxidant activity and NIR / pH dual responsiveness according to claim 6, characterized in that: When used as wound dressing, the power density is 2 W cm -2 The concentration of hollow CuS NPs was 125 μg / mL using 808 nm near-infrared laser.
Citation Information
Patent Citations
Method for preparing copper sulfide hollow sphere
CN101054197A
PH-responsive composite nano material based on hollow copper sulfide and ruthenium complex, preparation method of nano material and application of nano material in medicines for treating cancers
CN110384799A
Polyacrylamide-quaternized chitosan / EGCG (epigallocatechin gallate) hydrogel as well as preparation method and application thereof in back wound healing
CN117304547A
Extracellular matrix bionic deferoxamine copper sulfide hydrogel as well as preparation method and application thereof
CN118045223A
Photo-thermal antibacterial hydrogel wound dressing and preparation method thereof
CN118304464A
Cited By
Dithioformate-metal coordination two-dimensional network material, composite hydrogel and application thereof
CN121086263A